2015
DOI: 10.1007/s00170-015-8228-2
|View full text |Cite
|
Sign up to set email alerts
|

Arc characteristics and metal transfer modes in arcing-wire gas tungsten arc welding

Abstract: Arcing-wire gas tungsten arc welding is an innovative process developed as a variant of gas tungsten arc welding to reinforce the deposition rate by utilizing bypass arc energy. After establishing an experimental platform, the experiments were conducted to study the arc characteristics, interaction of the main and bypass arcs, and metal transfer behavior. Magnetic arc blow, location of the bypass arc root, and shielding gas flow were found to cause arc deflection and an invisible obstacle between the arcs in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In the MIG/MAG process, the objective is to obtain an optimal metal transfer with minimal heat introduced into the parts. The evolution has been carried out through the following variants: CMT (Cold Metal Transfer, from Fronius) that detects a short circuit with digital process control and detaches the droplet by retracting the wire, during welding [1,2]; SST (Surface Tension Transfer, from Lincoln Electric) that combines high-frequency inverter technology with advanced "Waveform Control Technology" in place of traditional short-arc GMAW welding [3]; RMD (Regulated Metal Deposition, from Miller) [4]; Wise solutions (terms WiseRoot, WiseThin and FastRoot, from Kemppi) [5]; the pulsed arc with developments by most welding machine manufacturers. The pulsed arc is based on the simplified rectangular wave (pulsed MIG, MIG-P or P-GMAW) [6], Figure 1, with peak intensity at a high value and average time as low as possible.…”
Section: Innovation In the Mig Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In the MIG/MAG process, the objective is to obtain an optimal metal transfer with minimal heat introduced into the parts. The evolution has been carried out through the following variants: CMT (Cold Metal Transfer, from Fronius) that detects a short circuit with digital process control and detaches the droplet by retracting the wire, during welding [1,2]; SST (Surface Tension Transfer, from Lincoln Electric) that combines high-frequency inverter technology with advanced "Waveform Control Technology" in place of traditional short-arc GMAW welding [3]; RMD (Regulated Metal Deposition, from Miller) [4]; Wise solutions (terms WiseRoot, WiseThin and FastRoot, from Kemppi) [5]; the pulsed arc with developments by most welding machine manufacturers. The pulsed arc is based on the simplified rectangular wave (pulsed MIG, MIG-P or P-GMAW) [6], Figure 1, with peak intensity at a high value and average time as low as possible.…”
Section: Innovation In the Mig Processmentioning
confidence: 99%
“…The pulsed arc is based on the simplified rectangular wave (pulsed MIG, MIG-P or P-GMAW) [6], Figure 1, with peak intensity at a high value and average time as low as possible. The solution for the transfer of a droplet during the impulse is controlled by a synergistic mode [7,8] and governed by the relationship (1), where T is the period, d is the droplet detachment constant and the constant n = 1.1 to 2.…”
Section: Innovation In the Mig Processmentioning
confidence: 99%
“…A standard GTAW setup comprises of (a) a DC/AC power source which delivers the welding current, (b) a welding torch having a tungsten electrode and gas nozzle (as shown in Fig. 2) [39][40] and (c) inert shielding gas (Ar) supply shields the molten metal pool. The details of the conditions used in GTAW process is shown in Table - The plates after depositing Zn layer through GTAW need to be subjected to various tests to establish composition of processed region.…”
Section: Figure -2: Pictorials and Schematic Of Details Of Experiment...mentioning
confidence: 99%
“…HWGTAW is suitable for automation and can join variety of materials without much difficulty. [17][18][19][20][21][22] Padmanaban et al 23 demonstrated the welding characteristics in joining 304H super austenitic stainless steel tubes of 4.4 mm thickness and presented a welding window for obtaining successful joints. Olivares and Dı´az 24 joined SAE 1020 steel and found that the current passing though the preheated filler wire and polarity significantly influenced the degree of arc blow.…”
Section: Introductionmentioning
confidence: 99%